PENGEMBANGAN KINERJA PERBANKAN SYARIAH BERDASARKAN MODEL MAQĀṢID AL-SHARĪ‘AH - Hartomi Maulana; Setiawan Bin Lahuri; Soritua Ahmad Ramdani Harahap (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
This study aims to explain the performance development in BRISyariah Ponorogo with the maqāṣid al-sharī‘ah model. This study uses a qualitative research methodology with the object of research at BRISyariah Ponorogo. The results of this study indicate that BRISyariah Ponorogo refers to the five aspects described by Al-Ghazali in preservating of religion, soul, mind, progeny and wealth. The application is seen from the commitment of BRISyariah Ponorogo in maintaining the sharia of all products from the culture of usury practice.